Dry Reforming of Methane over Ni/γ‐MgO Catalysts in a Coaxial Dielectric Barrier Discharge Reactor. Issue 4 (16th February 2021) - Farshidrokh, Zahra; Khani, Mohammad Reza; Khodadadi, Abbasali; Gharibi, Mahtab; Shokri, Babak
Abstract: Dry reforming of methane (DRM) over Ni/ γ ‐MgO catalysts in a coaxial dielectric barrier discharge (DBD) reactor was investigated and compared with DRM without catalysts. Firstly, the catalysts Ni/MgO, Ni/5%CeO2 /MgO, and Ni/7%CeO2 /MgO were prepared, their characteristics were specified by X‐ray diffraction, and then, they were partially packed into the DBD reactor. Various parameters such as the discharge power, flow rate, and CH4 /CO2 molar ratio were explored. The presence of catalysts in the plasma reactor increased the yield and selectivity of H2 and CO. Furthermore, the effect of a reduced catalyst (Ni/7%CeO2 /MgO reduced in argon‐hydrogen plasma) was evaluated, showing that CH4 can be converted with activated catalyst without extra power. Activated Ni/7%CeO2 /MgO alone was able to convert CH4 to over 99 % for 30 min after reduction. Abstract : CH4 and CO2, two main greenhouse gases, were converted to H2 and CO by dry reforming of methane using a combination of plasma and a Ni‐based catalyst and with CeO2 as promoter to achieve higher conversion rates. Variations in power, CH4 /CO2 molar ratio, and flow rate were studied for both plasma alone and plasma with catalyst. The catalyst/plasma combination improved the CH4 conversion to over 90 %.